A rare case of early onset intrahepatic cholestasis of pregnancy - L., Saraswathi H.; Joshi, Trishula Gurunath; Ganta, Suvarna Jyothi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Intrahepatic cholestasis of pregnancy (ICP) is an important complication of pregnancy requiring increased surveillance by the obstetricians due to its increased foetal morbidity and mortality in the form of preterm birth, foetal distress, RDS including sudden IUD and stillbirth. The incidence of ICP is increasing due to IVF and routine administration of progesterone in early pregnancy. ICP usually presents in late second and third trimester. Here authors are presenting a case of early onset ICP (14 weeks) which developed in an IVF conception.